Evaluation of Cervical Cancer Screening in Japan: Challenges and Future Directions for Negative Intraepithelial Lesion or Malignancy/High-Risk Human Papillomavirus Positive Case Management - Yasushi Umezaki; Asako Fukuda; Makiko Kurihara; Mariko Hashiguchi; Kaoru Okugawa; Masatoshi Yokoyama (Current Oncology)
Cervical cancer screening is crucial for early detection and prevention. In Japan, women with negative intraepithelial lesion or malignancy (NILM) and high-risk human papillomavirus (HR-HPV) positivity are recommended retest for 12 months, rather than immediate colposcopy. International guidelines differ, and often prioritize early colposcopy for persistent HPV16/18 infections. This study evaluates Japan’s current screening approach, and identifies areas for improvement. A retrospective cohort study analyzed cervical cancer screening data from Saga Prefecture (2019–2021), assessing follow-up adherence, colposcopy referral rates, and CIN2+ and CIN3+ detection among NILM/HR-HPV+ cases. Among 27,789 individuals screened, 2248 (8.1%) were NILM/HR-HPV+. Follow-up adherence after 12 months was 54.4%. Of these, 132 with cytological abnormalities underwent colposcopy, revealing CIN2+ in 27.3% of cases. Additionally, 561 women with persistent NILM/HR-HPV+ underwent colposcopy, with CIN2+ in 7.6% and CIN3+ in 3.9% of cases. Japan’s current NILM/HR-HPV+ management strategy could delay the detection of high-grade cervical lesions. International guidelines favor earlier colposcopy referrals, particularly for HPV16/18+ cases. To improve cervical cancer prevention, Japan should consider a risk-based stratification model, enhance follow-up adherence, expand colposcopy access, and develop a national patient tracking system. Adopting primary HPV-based screening could attain the best global practices, facilitating earlier detection and reducing cervical cancer.